Chinese Management Buyouts and Board Transformation - Li, Yao (Journal of business ethics, 2010)
We assess the extent to which Chinese MBOs of listed corporations enable a balance to be achieved between facilitating growth and supporting the interests of minority shareholders other than the buyout organization. Using novel, hand-collected data from 19 MBOs of listed corporations in China, a matched sample of 19 non-MBOs and the population of listed corporations, we examine the extent to which boards of directors are changed to bring in executive and outside directors with the skills to grow as well as restructure a business. We also examine the extent to which outside directors become involved in actions to develop the business rather than actions related to fostering the interests of all shareholders. We find in fact little evidence that outside board members have the skills to add value to the MBO firms. Boards appear to focus mainly on related-party transactions with some more limited attention to growth strategies. Outside directors do not seem to openly disagree with incumbent managers on the disclosure of their actions but may express their views and exert pressure behind the scenes.